Bimbingan Islam Untuk Menumbuhkan Kepercayaan Diri Disabilitas Netra Postnatal - Dhiyaul Fitriyani, Putri; Mutaqin, Zainal; Zaenal Abidin, Isep (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2015)
The visually impaired are individuals who have limited vision, which causes the individual to be unable to see like normal people in general. The purpose of this study was to determine the process of Islamic guidance in growing self-confidence for postnatal blindness in the Indonesian Muslim Blind Association at the Indonesian Muslim Blind Association. This study uses a descriptive method with a qualitative approach. Data collection techniques used are observation and interviews. The data sources in this study consisted of primary data, namely postnatal blind mentors and persons with disabilities, blind conditions and the programs of the Indonesian Muslim Blind Association. Then for secondary data, namely documents, journal articles, books, magazines and other sources relevant to Islamic guidance, self-confidence, and blindness. The conclusion of this study is that the condition of the visually impaired previously experienced many problems. After participating in the programs at the Indonesian Muslim Blind Association, they are able to live with self-confidence.